Development of Estimation Methods of Skin Oxidation and Evaluation of Anti-Oxidative Effects of Genistein in Topical Formulations - Kim, Seong Yeon; Kim, Dongju; Kim, Yeongseok; Kim, Hyeong Min; Hwang, Sung-Ha; Kwak, Jiyeon; Kuh, Hyo-Jeong; Lee, Jaehwi (The Korean journal of physiology & pharmacology, 2012)
The objective of the present study was to establish the method of measurement of hydrogen peroxide and to estimate the anti-oxidative effect of genistein in the skin. UVB induced skin oxidation and anti-oxidative effect of genistein formulations were evaluated by determining levels of hydrogen peroxide. The mechanism involved in the determination of hydrogen peroxide is based on a color reaction between ferric ion (Fe(3+)) and xylenol orange, often called FOX assay and subsequent monitoring of absorbance values of the reactant at 540 nm. The reaction was to some extent pH-dependent and detection sensitivity was greatest at pH 1.75. Genistein liposomal gel demonstrated better anti-oxidative effect with regard to lowering hydrogen peroxide levels elevated by UVB irradiation compared to genistein-suspended gel. A linear relationship has been observed between anti-oxidative effect of genistein and drug deposition in the skin tissue. Genistein liposomal gel resulting in the localization of the drug in the deeper skin led to improved anti-oxidative effect compared to genistein gel. The suggested method for evaluation of oxidation of the skin can be used as a tool to screen effective anti-oxidative agents and their delivery systems acting on the skin.